Exploring Agricultural Zakat in Southeast Asia: A Fascinating Comparative Analysis (Contrarius Series: Law & Social Justice, 2026)
Agricultural zakat is an important tool within the Islamic economic system that has significant potential to enhance food security and reduce social inequality. However, its implementation at the national level often encounters regulatory and governance challenges. This study aims to conduct a comparative analysis of agricultural zakat regulations in Indonesia, Malaysia, and Brunei Darussalam, focusing on aspects such as nisab (the minimum threshold), zakat rates, types of crops subject to zakat, payment times, obligatory subjects, managing institutions, and the effectiveness of zakat utilization. The method employed is a comparative literature review that analyzes legal documents, zakat institution regulations, statistical reports, and relevant academic publications. The findings indicate that while the three countries share significant legal similarities, they differ in their institutional approaches: Indonesia relies on national legislation, though it faces low compliance challenges; Malaysia has relatively effective state regulations but experiences variations between regions; and Brunei maintains a consistent centralized system despite its smaller economic scale. This analysis confirms that the effectiveness of agricultural zakat is influenced more by institutional governance and community compliance than by differences in jurisprudential interpretations (fiqh). The study concludes that an integrative model that combines the strengths of national regulation, local institutional engagement, and consistent application of Sharia law is essential for developing agricultural zakat regulations in ASEAN.